The semantics of complex sentences in the discourse of health and diseases : a case study in Abui - Tee, Yuan Wen Alicia (2016)
Clause linking in natural discourse plays a crucial role in showing the relationship between events. In the theme of health and diseases, such relationships are especially important as certain illnesses manifest itself in a specific manner that reveals the identity of the disease to the trained eye. The data used in this paper was obtained from the corpus of interviews about personal health history collected in the Abui community of Takalelang, in Eastern Indonesia. It was found that Abui has a rich clause linking inventory, particularly elaborate in succession. The most common markers are are ba, ya, re, haba, mai, and maiye. These devices allow for the detailed descriptions of disease progression. This paper describes the semantics of clause linkers against a typological framework that is derived from Longacre (2007) and Dixon (2009). The paper aims to describe the types of clause linking in Abui and ultimately inform about the health situation in Alor. With a better understanding of Abui, we hope to improve the process and quality of healthcare provision to the Abui community as a whole.